The Urgency of Mastering Dhama'ir Rules in the Conditions for Becoming a Mufassir of the Qur'an - Roby Hably; Silvia Marina; Alfian Mubarok (Penerbit Hellow Pustaka, 2025)
A correct understanding of the Qur’an relies heavily on mastering the Arabic language, the original language of revelation. One of the most essential yet often overlooked linguistic aspects in Qur’anic interpretation is the use of pronouns (ḍamā’ir). In the Qur’an, pronouns not only serve as word substitutes but also significantly affect contextual understanding and meaning precision. This article aims to highlight the importance of mastering the rules of pronouns as a requirement (syurūṭ) for a qualified mufassir, while analyzing the forms, types, and referents (marjiʿ) of ḍamīr in the Qur’an.This study employs a qualitative-descriptive approach through library research. Data were collected from the Qur’an, classical and contemporary tafsir literature, and Arabic grammar books focusing on pronouns. The analysis was conducted using content analysis, involving identification of verses containing ḍamīr, classification of their forms and syntactic roles, and examination of contextual referents to ensure accurate interpretation.The findings reveal that ḍamīr in the Qur’an appear in various forms (explicit and implicit), each governed by specific grammatical rules. Understanding the referent (marjiʿ) is crucial, as misidentifying it may lead to flawed interpretation. The study also uncovers special grammatical principles regarding pronouns, including rhetorical devices such as ḍamīr al-sha’n, ḍamīr al-faṣl, and implied referents, which differ from the conventions in other languages. Thus, mastering the rules of pronouns is an indispensable requirement for every Qur’anic exegete, as affirmed by experts in Qur’anic sciences and Arabic linguistics